Escaping Two Dictators: Czechoslovakian Intelligence Defectors from the New Communist Regime, 1948-1949. Issue 3 (1st September 2020) - Riehle, Kevin
ABSTRACT: The Soviet-sponsored communist takeover of Czechoslovakia in February 1948 prompted hundreds of government officials to seek opportunities to escape or to remain abroad. Among those who sought opportunities to escape were nine Czechoslovakian military intelligence officers from the Main Staff Second Directorate, who defected to American or British occupation forces in Germany and Austria from March 1948 to May 1949 (see Table 1 ). Based on these lives of these officers as reflected in archival records, this article pieces together a picture of early communist Czechoslovakian intelligence targets, communist suspicion of Western allies, and the officers' motivations for leaving their intelligence positions, to show the effects of the communist takeover of Czechoslovakian on intelligence officers and operations.